The incidence and extraction causes of third molars among young adults in Poland - Tomaszewska, Agnieszka; Sikora, Mateusz (Anthropological Review, 2019)
Despite many years of observation, the issue of third molars is still open for discussion. Among human teeth, third molars vary the most in number and morphology, which results from genetic changes and environmental factors affecting the evolution of the human dentition. This research aims to study various aspects of third molars in the population of young Poles, such as the incidence, time of eruption and causes of extraction in men and women. The analyses consider the socio-economic status of the respondents, including the frequency of visits to the dentist. Eight hundred students, aged 19–25 (14.4% of men and 85.6% of women) of the universities located in Wroclaw, Poland, took part in an online questionnaire survey. The incidence of third molars was smaller in the women (32.4–34.9%) than in men (47.8–56.5%) (p<0.001). For both sexes, the most frequent causes of extraction were abnormal tooth position (29.6–54.5%) and orthodontic treatment (15.5–27.3%). Both incidence and causes of extraction were related for all the examined pairs of teeth (upper–lower teeth and right–left teeth). The men (17.94–18.49 year) and women (18.42–18.83 year) did not differ in the mean age of their third molars’ eruption. The men visited the dentist less often than the women did (p<0.001). The study presents original research and confronts it with published results. Despite the limitations of an online survey, the results can contribute to more advanced research conducted on a larger scale. In particular, more detailed research is recommended for the Polish population, for which such studies are scarce.